SEARCHING FOR SOUNDS IN U.S. LITERATURE: A MULTISENSORIAL, MULTIDISCIPLINARY PROJECT - Alessandra Calanchi (European Scientific Journal, ESJ, 2015)
The aim of this essay is to provide a contribution to soundscape studies from the standpoint of U.S. literature and from a multi-disciplinary approach. The six case studies here included are the result of a project carried out by two groups of upper graduate students and myself during the academic years 2012-2013 and 2013-2014 at the Department of International Studies of the University of Urbino, Italy.1 We examined a selection of literary texts (from the 17th through the 189th century), searching for sounds, noises, silence, talk, conversation, bird songs, whistles, rattles, thunders, etc. with the aim of re-mapping the literary canon from an aural perspective. Given such an ambitious aim, we first had to study the ABC of acoustics, then practise the sound lexicon, and finally match our practical knowledge to the words we found on the written – and seemingly dumb – pages of our books. By reading aloud, both individually and in class, and by discussing our sensations, perceptions, and reactions to the soundscapes we encountered, we slowly discovered a universe which was full of sound and meanings. To this universe we applied the notions we had learnt from scholarly books, relying on the classification of sounds into categories (natural sounds or geophonies, sounds of life or biophonies, human-induced sounds or anthrophonies; see Schafer, Krause), the notions of low-fi and hi-fi soundscape (Schafer), the vibratory nature of sound (Di Benedetto), the findings of auditory neurosciences (Schnupp et al.), auditory spatial awareness (Blesser & Salter), and the concepts of acoustic territorialization, audible identity, and sonic body (Labelle). This essay is also a homage to electronic musician and soundscape pioneer Bernard L. Krause, b. 1938, who in 1968 founded Wild Sanctuary, an organization dedicated to the recording and archiving of natural soundscapes (www.wildsanctuary.com). He was the first to incorporate natural soundscapes as an integral component of orchestration, and in 2007 he demonstrated that it is possible to listen to soundscapes from all over the world and to create archives.